A review on intrusion detection approaches in cloud security systems. (25th June 2019) - Singh, Satyapal; Kubendiran, Mohan; Sangaiah, Arun Kumar
Cloud computing is a technology that allows the conveyance of services, storage, network, computing power, etc., over the internet. The on-demand and ubiquitous nature of this technology allows for its ease of use and availability. However, due to this very reason, the cloud services, platform or infrastructure remain to be a target for attackers. The most common attack is the one that tries to take control of one or more virtual machine instances running on the cloud. Since cloud and networking technologies go side by side, it is inevitable to keep such malicious attempts at bay. Nevertheless, Intrusion Detection Systems (IDS) are software that can detect potential intrusions within or outside a secure cloud environment. In this paper, a study of different IDS that have been previously proposed in order to mitigate or in best case eliminate the possible threats posed by such intrusions has been done.